How Do Financial Regulators Govern Their Financial Business: A Comparison of FSA in the UK and Regulatory Commissions in China - Tang, Qi (2009)
Financial regulation system is a critical topic as the financial industry is developing more and more rapidly. The UK is one of the earliest countries to start its financial reform and establish a single and independent commission called Financial Service Authority (FSA) to govern its financial business. The China Banking Regulatory Commission, Security Regulatory Commission and Insurance Regulatory Commission are the separated regulatory organizations in China. In this dissertation, the rationale of financial regulation is firstly outlined. Then the background of these agencies and the scandals in each country are described. Followed is the comparison of them, through which we can get the conclusion on how financial regulators should be and give suggestions to help improve the financial regulation and supervision of China.